The prognostic value of individual NT-proBNP values in chronic heart failure does not change with advancing age. Issue 10 (15th January 2009) - Frankenstein, L; Clark, A L; Goode, K; Ingle, L; Remppis, A; Schellberg, D; Grabs, F; Nelles, M; Cleland, J G F; Katus, H A; Zugck, C
Abstract : Background: It is unclear whether age-related increases in N-terminal pro-brain natriuretic peptide (NT-proBNP) represent a normal physiological process—possibly affecting the prognostic power—of NT-proBNP—or reflect age-related subclinical pathological changes. Objective: To determine the effect of age on the short-term prognostic value of NT-proBNP in patients with chronic heart failure (CHF). Design: Prospective observational study with inclusion and matching of consecutive patients aged >65 years (mean (SD) 73.1 (6.0) years) to patients <65 years (53.7 (8.6) years) with respect to NT-proBNP, New York Heart Association stage, sex and aetiology of CHF (final n = 443). Setting: University hospital outpatient departments in the UK and Germany. Patients: Chronic stable heart failure due to systolic left ventricular dysfunction. Intervention: None. Outcome measure: All-cause mortality. Results: In both age groups, NT-proBNP was a significant univariate predictor of mortality, and independent of age, sex and other established risk markers. The prognostic information given by NT-proBNP was comparable between the two groups, as reflected by the 1-year mortality of 9% in both groups. The prognostic accuracy of NT-proBNP as judged by the area under the receiver operating characteristics curve for the prediction of 1-year mortality was comparable for elderly and younger patients (0.67 vs 0.71; p = 0.09). Conclusion: NT-proBNP reflects disease severity in elderly and younger patients alike. In patients with chronic stable heart failure, the NT-proBNP value carries the same 1-year prognostic information regardless of the age of the patient.